Group Counseling with Cognitive Behavior Therapy (CBT) Approach to Improve Students' Literacy and Paraphrasing Ability - Leorince Leorince (Bisma The Journal of Counseling, 2022)
Postmodern-era education requires critical abilities. High school students are not only required to memorize and understand the subjects presented by the teacher. However, they can analyze the usefulness of subjects in everyday life critically. The students consider this task heavy because their literacy and paraphrasing skills are still deficient. Therefore, group counseling is needed so that high school students literacy and paraphrasing skills are proficient. The method used is group counseling with a Cognitive Behavior Therapy (CBT) approach. The research method used is descriptive qualitative. The results of the study indicate that the literacy and paraphrasing skills of high school students are improved by (i) directing the use of social media properly and correctly in the classroom; (ii) training by direct practice in the learning process and through assignments that can include the application of paraphrasing; and (iii) being a role model in reading and paraphrasing information.